Adaptive mechanisms to drought risk management in a KwaZulu-Natal community, South Africa - Vuyiswa Khumalo; Hloniphani Moyo; Lutendo Mugwedi; Johanes Belle (Jàmbá)
Households in developing countries have established various informal mechanisms to cope with unanticipated disasters such as droughts. Understanding these strategies in the context of climate change will enhance the design of locally applicable adaptation mechanisms. This study aimed to investigate a South African rural community’s adaptive mechanisms during- and ex-post-drought. Questionnaires were administered to 200 household heads, and five focus group discussions were held with selected community members. An index was computed to establish each adaptive mechanism’s importance (termed the rank order) relative to its use in the study area. During droughts, borrowing from neighbours was the most commonly used mechanism by households with no savings, while sharecropping was the second most used mechanism. Ex-post-droughts, using savings was the primary strategy for community members who had savings, followed by seeking employment as the second most used strategy.